Impact of near infrared light in pediatric blood drawing Centre on rate of first attempt success and time of procedure. - Conversano, Ester; Cozzi, Giorgio; Pavan, Matteo; Minute, Marta; Gortan, Elena; Montico, Marcella; Vecchi Brumatti, Liza; Ronfani, Luca; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Peripheral blood access and venipuncture are a stressful and painful experience in pediatric patients; moreover, it is estimated that more than one attempt is required to achieve the procedure in about one third of children. For this reason, we investigated if Near-infrared light technology routinely used, could give an advantage to venipuncture in a pediatric blood center setting. METHODS: We conducted an open, pseudo-randomized controlled trial with two parallel arms, in the blood-drawing center, with enrolment of 115 patients between 0 and 18 years, in 14 consecutive working days. Fifty-three subjects were enrolled in group 1 (VeinViewer®) and 62 in group 2 (control group). We divided patients into three subgroups considering their age (< 5 years, 6-10 years, > 10 years). The primary study outcome was to assess if the use of VeinViewer® was associated with a reduction of time to perform blood sampling. The secondary outcome was to analyze VienViewer®'s impact on first attempt success rate in blood sampling. RESULTS: No difference was found regarding the duration of blood sampling between the two groups, even after stratifying the patients into the three age subgroups. There was no difference between the two groups in the success at the first attempt in blood sampling. CONCLUSIONS: Routine use of VeinViewer® is not useful to reduce time of the procedure during venipuncture. TRIAL REGISTRATION: The study was registered with ClinicalTrials.gov, with number NCT03277092 , on September 8, 2017.
Keywords: Adolescent; Age Factors; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Infrared Rays; Lighting; Male; Phlebotomy; Time Factors

An unusual unilateral breast enlargement in a prepubertal girl. - Pavan, Matteo; Faleschini, Elena; Tornese, Gianluca; Zandonà, Lorenzo; Ventura, Alessandro (Arch Dis Child, 2018)

Extremely large air distension of the bowel. - Pavan, Matteo; Ventura, Giovanna; Maschio, Massimo; Ventura, Alessandro (Lancet, 2015)
Keywords: Adolescent; Air; Biopsy; Female; Hirschsprung Disease; Humans; Intestine, Large; Rectum

A girl with photosensitivity and hepatic steatosis. - Pavan, Matteo; Gortani, Giulia; Rubinato, Elisa; Faletra, Flavio; Pastore, Serena; Ventura, Alessandro (J Pediatr, 2014)
Keywords: Child; Diagnosis, Differential; Fatty Liver; Female; Humans; Photosensitivity Disorders; Protoporphyria, Erythropoietic